Systematic Literature Review: The Obstacles of Madrasah Aliyah Students Facing Maharatul Qiraah - Robithah Aulia; Sofyan Sauri; Asep Sopian (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2025)
Reading proficiency is one of the important aspects of language learning. Arabic language assessment is also assessed through the individual's reading proficiency. Obstacles found in one Arabic language learning proficiency are aspects that need to be considered. Students experience obstacles that affect their learning achievement. Having an in-depth identification of the problems of maharah qiraah will make it easier for teachers to teach Arabic. This study uses a qualitative approach with a systematic literature review method. Data sources are obtained from the results of research conducted by other researchers. This is done so that researchers can access more information about the problems of maharah qiraah. To produce relevant research, researchers select articles published in the last five years. Data search uses "Publish or Perish" and also "Google Scholar." Data selection is based on keywords that researchers have determined. Data collected through the two software programs will be selected for as many as seven studies. The selection is based on three important aspects, namely topic relevance, research quality, and also the year of publication. The obstacles faced by both teachers and students are equally important to know. Achievement in learning does not only depend on the teacher but also the students. Each component is involved in achieving learning goals. One of the things that teachers can do to improve students' reading skills is to implement peer groups so that they can improve each other's reading. This study is expected to help teachers find the right solution in dealing with the problem of maharah qiraah